Influence of sorghum inclusion in fattening steers diets on health and fatty acids profile of Longissimus dorsi muscle - VOICU, DORICA; VOICU, I; VASILACHI, ANDREEA; UTA, R A; MIHALCEA, T; PELMUS, RODICA STEFANIA (The Indian Journal of Animal Sciences, 2016)
The study was conducted using 21 Romanian Black Spotted fattening steers to determine the effects of sorghum grains on health and fatty acid profile of Longissimus dorsi muscle. The animals were assigned uniformly to 3 groups of 7 steers each, which received different treatments: control (C) received a compound feed without sorghum grains, experimental group (E1) received 15% sorghum grains in the compound feed, while next experimental group (E2) received 25% sorghum grains in the compound feed. To determine the biochemical parameters, blood samples were collected from animals at the end of experimental period. The laboratory analyses conducted on samples of Longissimus dorsi muscle collected from the 3 experimental groups, showed changes in the fatty acid composition. The proportion of saturated fatty acids (SFA) decreased in favour of the unsaturated fatty acids (UFA) with 1.04% in group E2, while the proportion of unsaturated fatty acids increased from 53.00% in the control group to 54.19% in group E2.